The duration and body position during tongue-kissing among heterosexual men and women - Tran, Julien; Fairley, Christopher K.; Ong, Jason J.; Bradshaw, Catriona S.; Aung, Ei T.; Maddaford, Kate; Chen, Marcus Y.; Hocking, Jane S.; Chow, Eric P. F. (Frontiers in Public Health, 2022)
Background Emerging data suggest tongue-kissing may transmit gonorrhea. We aim to examine the duration or body position of heterosexual men and women during tongue-kissing (henceforth, known as kissing). Methods A cross-sectional survey among heterosexual men and women attending the Melbourne Sexual Health Centre in Australia between May 2019 and March 2020 collected data on the duration and body position (i.e., on top of or lying down underneath) of their most recent kissing partner in the past 3 months. Univariable and multivariable linear regressions were performed to examine the association between gender and kissing duration. Results Of 2,866 individuals, 93.6% (n = 2,683) had at least one kissing partner in the past 3 months, which included 1,342 (50.1%) men and 1,341 (49.9%) women, and 87.2% (n = 2,339) had sex with their opposite-gender kissing partner. The adjusted mean duration of kissing with the most recent opposite-gender kissing partner did not differ between men and women (12.2 vs. 11.5 min, p = 0.170). More men were on top of their most recent opposite-gender kissing partner compared to women (87.9 vs. 82.9%, p < 0.001). Men reported a longer kissing duration than women when they were on top of the opposite-gender kissing partner (8.3 vs. 7.4 min, p = 0.006). More women had same-gender kissing partners than men (9.6 vs. 2.8%, p < 0.001). Conclusion Men spending longer than women on top of their opposite-gender kissing partner suggests a potential alternative explanation for oropharyngeal gonorrhea being seen more commonly in women. Further research should investigate whether body positioning and duration of kissing influence the risk of gonorrhea transmission.